PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SPRING BED COMFORTA - Rika Sylvia; Ni Nyoman Suarniki; Masrani Noor; Melyanie Melyanie (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aims to analyze the influence of product quality, price, and promotion on the purchasing decision of Comforta Spring Bed at PT Massindo Solaris Nusantara Banjarmasin. The background of the research is based on the increasingly fierce competition in the spring bed industry and the changing consumer behavior, with customers becoming more critical in selecting products. This research uses a quantitative approach involving 50 consumers who have a Comforta Spring Bed. Data were collected through questionnaires and analyzed using amultiple linear regression. The results show that product quality, price, and promotion have a significant influence, both simultaneously and partially, on purchasing decisions. These three variables explain 91.2% of the variation in consumer purchasing decisions. The findings emphasize the importance for companies to improve product quality continuously, offer competitive prices, and carry out effective and sustainable promotions to increase sales and customer loyalty.